2011
DOI: 10.1007/s00418-011-0888-x
|View full text |Cite
|
Sign up to set email alerts
|

The lipid droplet coat protein perilipin 5 also localizes to muscle mitochondria

Abstract: Perilipin 5 (PLIN5/OXPAT) is a lipid droplet (LD) coat protein mainly present in tissues with a high fat-oxidative capacity, suggesting a role for PLIN5 in facilitating fatty acid oxidation. Here, we investigated the role of PLIN5 in fat oxidation in skeletal muscle. In human skeletal muscle, we observed that PLIN5 (but not PLIN2) protein content correlated tightly with OXPHOS content and in rat muscle PLIN5 content correlated with mitochondrial respiration rates on a lipid-derived substrate. This prompted us … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
151
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 142 publications
(173 citation statements)
references
References 43 publications
19
151
3
Order By: Relevance
“…Here and in another recent study ( 44 ), PLIN5 protein expression was found to be elevated in muscles of exercisetrained humans. The precise function of this protein remains unclear, but several lines of evidence point to a key role for Plin5 in governing the spatial and metabolic interactions between lipid intramuscular droplets and their surrounding mitochondrial reticulum (45)(46)(47)(48).…”
Section: Resultsmentioning
confidence: 99%
“…Here and in another recent study ( 44 ), PLIN5 protein expression was found to be elevated in muscles of exercisetrained humans. The precise function of this protein remains unclear, but several lines of evidence point to a key role for Plin5 in governing the spatial and metabolic interactions between lipid intramuscular droplets and their surrounding mitochondrial reticulum (45)(46)(47)(48).…”
Section: Resultsmentioning
confidence: 99%
“…PLIN5 expression is also reported in pancreatic beta cells and hepatic stellate cells [35,36]. A unique feature with PLIN5 is that mitochondria are physically recruited to lipid droplets expressing high PLIN5 (Figure 2) [37,38]. Its expression is regulated by PPAR-alpha, and most importantly, PLIN5 plays roles in regulating cellular fat oxidation.…”
Section: Plin5mentioning
confidence: 84%
“…LDs [141], controlling both LD-TAG-derived FA release and facilitating its delivery to mitochondria for -oxidation [141,143,144]. Together, these observations indicate that mTAG pool turnover may dictate rates of FA oxidation as the majority of FA cycles through mTAG.…”
Section: Myocardial Triacylglycerol Lipolysismentioning
confidence: 95%